Ghost stories in late Renaissance France walking by night - Chesters, Timothy, 1976- (Oxford modern languages and literature monographs., 2011)
This work describes the ideological, intellectual, and literary role of ghost stories in late Renaissance France. It takes in prominent literary figures as well as lesser known tracts and pamphlets to shed light on the beliefs, fears, and desires of a period on the threshold of modernity.